TANNINS FROM SANGUISORBA OFFICINALIS AFFECT IN VITRO RUMEN METHANE PRODUCTION AND FERMENTATION - A. Cieslak; P. Zmora; A. Matkowski; I. Nawrot-Hadzik; E. Pers-Kamczyc; M. El-Sherbiny; M. Bryszak; M. Szumacher-Strabel (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to evaluate the effect of different doses of the Sanguisorba officinalis tannin extract (SOTE) on in vitro methane production, rumen microorganisms and basic rumen fermentation parameters. SOTE contained 451 mg g-1 of total tannins was tested at different doses (0, 1, 4, 10, 20, 40 and 100 mg of SOTE per vessel; the input of tannins was 0, 1.3, 5.1, 12.8, 25.6, 51.2, 128.0 g per kg dry matter, respectively) during 24 h fermentation of rumen fluid in batch culture system. The basal substrate consisted of meadow hay and barley meal (60:40 ratio). The rumen fluid was collected, pooled and mixed from three ruminally fistulated, Polish Holstein-Friesian dairy cows. The methane production was decreased significantly at the high doses (40 and 100 mg of SOTE per bottle). This favorable decrease at the highest dose (100 mg) was associated with the reduction of in vitro dry matter digestibility (IVDMD), Entodiniomorpha sp. and bacteria populations. The population of methanogens was not affected, as compared with the control treatment. These findings suggest that the highest dose of SOTE has a potential to reduce methane production by decreasing the protozoal population and IVDMD. However, the obtained data clearly showed the stimulating effect of the highest dose of tannins on ammonia release, 40 mg of SOTE should be used in further long-term studies. This dose indicated either antimethanogenic effect even when expressed per units of total gas production or volatile fatty acids. 40 mg of SOTE had no negative impact on in vitro rumen microbial populations, dry matter digestibility and volatile fatty acid content.
Keywords: methanogens; methane; rumen fermentation; Sanguisorba officinalis; tannins